2012
DOI: 10.1038/mt.2012.57
|View full text |Cite
|
Sign up to set email alerts
|

Ex Vivo Adenoviral Vector Gene Delivery Results in Decreased Vector-associated Inflammation Pre- and Post–lung Transplantation in the Pig

Abstract: Acellular normothermic ex vivo lung perfusion (EVLP) is a novel method of donor lung preservation for transplantation. As cellular metabolism is preserved during perfusion, it represents a potential platform for effective gene transduction in donor lungs. We hypothesized that vector-associated inflammation would be reduced during ex vivo delivery due to isolation from the host immune system response. We compared ex vivo with in vivo intratracheal delivery of an E1-, E3-deleted adenoviral vector encoding either… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
76
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 105 publications
(78 citation statements)
references
References 28 publications
2
76
0
Order By: Relevance
“…With EVLP, lungs are perfused and ventilated ex vivo at body temperature to mimic physiological conditions. EVLP can also facilitate delivery of a pharmacological, gene-or cell-based therapy to repair damaged lungs before transplant (23,40). We previously reported that intravenous clinical-grade, cryopreserved allogeneic human mesenchymal stem (stromal) cells (hMSC) were effective in restoring alveolar fluid clearance (AFC) in a human EVLP model of acute lung injury (ALI) induced by endotoxin or Escherichia coli bacteria (22,23).…”
mentioning
confidence: 99%
“…With EVLP, lungs are perfused and ventilated ex vivo at body temperature to mimic physiological conditions. EVLP can also facilitate delivery of a pharmacological, gene-or cell-based therapy to repair damaged lungs before transplant (23,40). We previously reported that intravenous clinical-grade, cryopreserved allogeneic human mesenchymal stem (stromal) cells (hMSC) were effective in restoring alveolar fluid clearance (AFC) in a human EVLP model of acute lung injury (ALI) induced by endotoxin or Escherichia coli bacteria (22,23).…”
mentioning
confidence: 99%
“…[27] In addition to reparative processes intrinsic to the lungs, Steen's solution, the most commonly used EVLP perfusate, has been specifically designed with a high colloid oncotic pressure in an effort to remove both interstitial and alveolar fluid from damaged lungs. [11] The EVLP platform also allows for physical manipulation with the removal of blood and secretions from the lungs; [10] biochemical manipulation with anti-inflammatory cytokines and vasodilatory agonists; [28][29][30][31] and cellular manipulation with mesenchymal stem cells. [32] In our study, we utilized the novel arginase inhibitor, ABH, in an effort to manipulate human lungs during EVLP.…”
Section: Discussionmentioning
confidence: 99%
“…In porcine models of ex vivo lung perfusion, adenoviral vector delivery has been demonstrated to be safe and effective. This therapy resulted in a decreased inflammatory response with better graft functionality after transplantation 31. In the area of renal research, Brasile et al previously demonstrated the ability to target an exogenous gene to the vascular endothelium of a kidney during NMP in a proof‐of‐concept experiment 32.…”
Section: Repair During Normothermic Machine Perfusionmentioning
confidence: 99%